Implementasi Bahasa Indonesia dalam Pengajaran Pendidikan Jasmani untuk Meningkatkan Efektivitas Pembelajaran - Ika Febriana; Febrina Panggabean; Ibrena Br Tarigan; Josua Al CH Sinaga; Win Sara Diwa (Populer: Jurnal Penelitian Mahasiswa, 2024)
This study aims to analyze the implementation of Indonesian language in teaching Physical Education and its impact on the effectiveness of learning in students of the Physical Education, Health, and Recreation Study Program. The use of Indonesian language as a medium of instruction is expected to improve students' understanding of concepts, involvement, and active participation in academic activities. This study collected data through observations and questionnaires distributed to third-semester students. The results of the study indicate that the effective use of Indonesian language in teaching physical education, health, and recreation contributes positively to students' understanding of the material, increases involvement in class discussions, and facilitates better communication between lecturers and students. These findings provide important insights for the development of teaching strategies at the higher education level, especially to improve the quality of learning in the field of Physical Education.